Associations of reallocating sedentary leisure-time to alternative discretionary movement behaviours with incident cardiometabolic diseases in 0.5 million Chinese adultsResearch in context - Paul J. Collings; Mengyao Wang; Harrison Hin Sheung Ho; Shiu Lun Au Yeung; Parco M. Siu; Benjamin J. Cowling; Stephen J. Sharp; Søren Brage; Nicholas J. Wareham; Huaidong Du; Derrick A. Bennett; Youngwon Kim (The Lancet Regional Health. Western Pacific)
Summary: Background: In Chinese adults, there is a considerable burden of sedentary behaviour. This study aimed to estimate the implications of reallocating sedentary leisure-time to non-sedentary behaviours for incident cardiometabolic diseases. Methods: A prospective cohort study of 462,370 Chinese adults (mean age 51 years; 59% female) who were free from diabetes and cardiovascular diseases at baseline. Isotemporal substitution Cox regression models were used to estimate the associations of reallocating self-reported sedentary leisure-time to the same amount of sleep, housework, Taichi, or conventional exercise (e.g., walking, jogging, ball games, swimming) with the risk of incident diabetes, stroke, and myocardial infarction (MI). The results are reported as adjusted hazard ratios and 95% confidence intervals per 30 min/day time exchanges. Potential impact fractions were calculated to estimate the proportional reductions in incident disease cases associated with time substitutions, assuming causality. Findings: During >5.25 million person-years of follow-up, 19,738 incident diabetes, 51,460 stroke, and 6767 MI cases were accrued. Lower disease risks were found for replacement of sedentary leisure-time by sleep (diabetes: 0.97 [0.95–0.99], stroke: 0.98 [0.97–0.99], MI: 0.97 [0.94–0.99]; in participants who slept <7 h/day), housework (diabetes: 0.97 [0.97–0.98], stroke: 0.99 [0.98–0.99], MI: 0.97 [0.95–0.98]), Taichi (diabetes: 0.97 [0.95–0.99], stroke: 0.98 [0.97–0.99], MI: 0.95 [0.92–0.98]), or conventional exercise (diabetes: 0.97 [0.95–0.99], stroke: 0.97 [0.95–0.98], MI: 0.92 [0.88–0.96]). Potential impact fractions ranged from an estimated 3.5% (95% confidence interval: 3.1–3.9%) fewer cases of incident stroke when replacing sedentary leisure-time with housework, to an estimated 9.6% (5.9–13.3%) fewer cases of incident MI when reallocating sedentary leisure-time to conventional exercise. Interpretation: Replacing sedentary leisure-time with behaviours such as housework, Taichi, sleep (in short sleepers) and conventional exercise is associated with lower risks of common cardiometabolic diseases in Chinese adults. Prevention strategies should be developed to promote movement behaviours and optimal levels of sleep at the expense of sedentary leisure-time. Funding: This analysis was supported by a Health and Medical Research Fund (HMRF) Research Fellowship (grant no: 06200087).